Is sustainable development achievable in Ghana? An analysis of Ghana's development policy achievements and challenges. (1st January 2012) - Domfeh, Kwame Ameyaw; Ahenkan, Albert; Bawole, Justice Nyigmah
Since the Stockholm Conference on the Human Environment in 1972 and the subsequent publication of the Brundtland report in 1987, Ghana has embarked upon the path of sustainable development (SD) through the development and implementation of policies deemed necessary to safeguard the environment and promote socio-economic development. Despite this commitment, the country is still characterised by poor environmental and human health, poverty, poor sanitation, low access to potable drinking water, energy, and high population growth. This paper uses sustainability frameworks to investigate the achievability of SD in Ghana. The key policies related to SD issues such as the environment, poverty reduction, health, water and sanitation, energy and population growth are analysed and the main achievements and challenges identified. The paper asserts that SD of Ghana could be a passing fad if issues confronting the country's sustainability are not addressed. The paper provides policy recommendations and strategies that will enable policy-makers to effectively tackle the SD challenges in the country.